2006
DOI: 10.1359/jbmr.060707
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Stimulates RANKL and Inhibits OPG Expression in Human Osteoblasts Through the MAPK Signaling Pathway

Abstract: Our study indicates that recombinant adiponectin induced RANKL and inhibited OPG expression in human osteoblasts through the AdipoR1/p38 MAPK pathway, and these responses contributed to the adiponectin-induced osteoclasts formation in the co-culture of osteoblast and peripheral blood monocytes systems. These findings showed that adiponectin increased osteoclast formation indirectly through stimulating RANKL and inhibiting OPG production in osteoblasts. It also suggests the pharmacological nature of recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
216
0
16

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(249 citation statements)
references
References 40 publications
(145 reference statements)
17
216
0
16
Order By: Relevance
“…We also found that age-and BMI-adjusted to the highest quartile versus the lowest quartile of adiponectin level had a significant association with lower OPG levels. This finding is consistent with previous in vitro [7] and in vivo studies [49].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We also found that age-and BMI-adjusted to the highest quartile versus the lowest quartile of adiponectin level had a significant association with lower OPG levels. This finding is consistent with previous in vitro [7] and in vivo studies [49].…”
Section: Discussionsupporting
confidence: 94%
“…via the p38 mitogen-activated protein kinase (MAPK) signaling pathway [43]. In contrast, adiponectin indirectly activates osteoclasts by stimulating RANKL and inhibiting OPG production in osteoblasts [7]. Adiponectin was associated with lower bone mass and decreased biomechanical measures of functional strength in growing mice [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, adiponectin has been shown to stimulate proliferation, differentiation, and mineralization of osteoblasts. (44) Moreover, adiponectin stimulates RANKL expression from osteoblasts and increases osteoclastogenesis, (45) whereas adiponectin knockout mice have increased bone mass. (46) In addition, TNF-a is among the most potent of the osteoclastogenic cytokines produced in inflammation via its receptors on stromal or osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that leptin as well as adiponectin can modulate bone metabolism [115,116,117].…”
Section: Resistin and Bone Metabolismmentioning
confidence: 99%